(untitled) (Environment & Health, 2022)
Objective: We determined the morphological indicators of 12-year-old schoolchildren in Lviv, established the differences between the anthropometric parameters of the children’s population from other large cities of Ukraine, and assessed the trends in physical development changes over a long period. Materials and methods: According to the conventional methods of anthropometry, we examined 348 12-year-old schoolchildren (including 172 boys and 176 girls) studying at Lviv city general education institutions. Results: Gender peculiarities of morpho-functional development of 12-year-old schoolchildren in the large cities of Ukraine were revealed. They reflect the active endocrine remodeling of children, which is primarily inherent in the performance of girls. The values of individual anthropometric parameters, both among boys and girls, were determined to be significantly higher (p